Berberine acts as a natural inhibitor of Wnt/β‐catenin signaling—Identification of more active 13‐arylalkyl derivatives. (24th August 2013) - Albring, Kai Frederik; Weidemüller, Julia; Mittag, Sonnhild; Weiske, Jörg; Friedrich, Karlheinz; Geroni, M. Cristina; Lombardi, Paolo; Huber, Otmar
Abstract Aberrant activation of the canonical Wnt/β‐catenin signaling pathway has been reported for numerous tumors of different origins. In most cases, mutations in components of the Wnt signaling pathway or in β‐catenin itself were detected which ultimately induce a genetic program that promotes cell proliferation and attenuates apoptosis. Thus, targeting of Wnt/β‐catenin signaling is of specific therapeutic interest. Herein, we investigated the plant‐derived isoquinoline alkaloid berberine, which has been reported to have anticancer activity, and synthetic 13‐arylalkyl derivatives thereof for their effects on Wnt/β‐catenin signaling. Berberine did not show major effects on viability of HEK‐293 embryonic kidney and HCT116 colon carcinoma cells and was not toxic in concentrations up to 20 µM. Berberine inhibited β‐catenin transcriptional activity and attenuated anchorage‐independent growth. As a result of berberine treatment, cellular levels of active β‐catenin were reduced concomitant with an increase in the expression of E‐cadherin. However, in unstimulated cells, the effects on β‐catenin levels were low. A screen of synthetic 13‐arylalkyl berberine derivatives identified compounds exhibiting activities superior to those of the naturally occurring parent substance with more than 100‐fold lower EC50 values for Wnt‐repression. Thus, berberine and its synthetic derivatives represent potential therapeutic agents to inhibit Wnt/β‐catenin signaling in tumorigenesis. © 2013 BioFactors, 39(6):652–662, 2013